Răspuns :
Sn=8*n^2-6*n
S(1)=8*1^2-6*1=8-6=2
S(2)=8*2^2-6*2=32-12=20
S(1)=a₁ =2
S(2) -S(1) =a₁+a₂ -a₁ =a₂ =20-2 =18
a₂=a₁+r
18=2+r
r=16
a₂₀₁₆ =2+(2016-1)×16)=2+32240=32242
S(1)=8*1^2-6*1=8-6=2
S(2)=8*2^2-6*2=32-12=20
S(1)=a₁ =2
S(2) -S(1) =a₁+a₂ -a₁ =a₂ =20-2 =18
a₂=a₁+r
18=2+r
r=16
a₂₀₁₆ =2+(2016-1)×16)=2+32240=32242
a(n)= S(n)-S(n-1)
an=8n^2-6n-[8(n-1)^2-6(n-1)]
an=8n^2-6n-[8(n^2-2n+1)-6n+6]
an=8n^2-6n-8n^2+16n-8+6n-6
an=16n-14
r=a(n+1)-a(n)
r=16(n+1)-14-16n+14
r=16
a(1)=16-14=2
a(2016)=a(1)+2015x16=32242
an=8n^2-6n-[8(n-1)^2-6(n-1)]
an=8n^2-6n-[8(n^2-2n+1)-6n+6]
an=8n^2-6n-8n^2+16n-8+6n-6
an=16n-14
r=a(n+1)-a(n)
r=16(n+1)-14-16n+14
r=16
a(1)=16-14=2
a(2016)=a(1)+2015x16=32242